The modified artificial cohort method for three dominant pelagic copepods in the northern North Pacific revealed species-specific differences in the optimum temperature - Teraoka, Takumi; Nagao, Shuya; Matsuno, Kohei; Yamaguchi, Atsushi (Frontiers in Marine Science, 2024)
The most concerning recent ocean changes in temperature issues are known as marine heat waves. Under these conditions, it is important to evaluate the effects of temperature on zooplankton. In this study, we investigated the growth rates of three dominant copepod species (Eucalanus bungii, Metridia pacifica, and Neocalanus plumchrus) in the northern North Pacific under three different temperature conditions (3, 7, and 11°C) using an artificial cohort method. Experimental conditions for 42 hour incubations were set to light intensity and photoperiod corresponding to 50 m depth. The dissolved oxygen solubility after rearing ranged from 69.2% to 102.1%, suggesting sufficient conditions for copepod growth. Chlorophyll a increased in 83% of the experiments, indicating that the food conditions were sufficient for the copepods. The mean proportion of dead specimens evaluated using neutral red was 10.2%, corresponding with the reported values in the field. Thus, it can be concluded that the laboratory-rearing conditions used in this study provided sufficient food, and the only effect evaluated would be that of the three different temperatures. Since the developmental time for each stage is longer than the rearing period, it is important to conduct experiments with a large number of individuals to obtain accurate growth rate results. The specific growth rates of E. bungii and M. pacifica increased with increasing temperature. In contrast, N. plumchrus showed the highest growth rate under moderate water temperature conditions. In terms of weight units (dry, carbon, and nitrogen), the carbon weight-specific growth rates were higher than those of the other two units, a common characteristic of the three species. This reflected lipid accumulation during the late copepodite stages. The interspecies differences in growth rate responses to water temperature reflect species-specific differences in temperature tolerance or the optimum temperature for each species. As E. bungii and M. pacifica reproduce near the surface layer through income breeding, their temperature tolerance or optimum temperature is expected to be high. However, because the reproduction of N. plumchrus occurs in the cold deep layer by using capital breeding, its temperature tolerance and optimum temperature would be lower than those of the former two species.